2020
DOI: 10.1073/pnas.2002307117
|View full text |Cite|
|
Sign up to set email alerts
|

Using synthetic biology to overcome barriers to stable expression of nitrogenase in eukaryotic organelles

Abstract: Engineering biological nitrogen fixation in eukaryotic cells by direct introduction ofnifgenes requires elegant synthetic biology approaches to ensure that components required for the biosynthesis of active nitrogenase are stable and expressed in the appropriate stoichiometry. Previously, the NifD subunits of nitrogenase MoFe protein fromAzotobacter vinelandiiandKlebsiella oxytocawere found to be unstable in yeast and plant mitochondria, respectively, presenting a bottleneck to the assembly of active MoFe prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
(73 reference statements)
2
28
0
Order By: Relevance
“…These features may explain why the process was never co-opted from microbes during plant evolution. Nonetheless, progress has been made toward this objective (Burén et al, 2017;Burén and Rubio, 2018;Eseverri et al, 2020;Xiang et al, 2020), and such work is testing and extending our understanding of BNF. Given the current state of knowledge and technology, the greatest impediment to solving the N problems of agriculture through N fixing plants may turn out to be public acceptance of such technology rather than our ability to develop it.…”
Section: Engineering Bnf Through Microbial Association and Direct Genetic Manipulationmentioning
confidence: 99%
“…These features may explain why the process was never co-opted from microbes during plant evolution. Nonetheless, progress has been made toward this objective (Burén et al, 2017;Burén and Rubio, 2018;Eseverri et al, 2020;Xiang et al, 2020), and such work is testing and extending our understanding of BNF. Given the current state of knowledge and technology, the greatest impediment to solving the N problems of agriculture through N fixing plants may turn out to be public acceptance of such technology rather than our ability to develop it.…”
Section: Engineering Bnf Through Microbial Association and Direct Genetic Manipulationmentioning
confidence: 99%
“…To date, functional NifH, NifU, and NifB have been purified from mitochondria of aerobically cultured Saccharomyces cerevisiae cells 10 , 11 , while active NifU and NifH were isolated from chloroplasts of Nicotiana benthamiana at the end of the dark period 12 . Also, the reported low stability of the NifD protein 13 has now been improved in two recent studies that identified key residues in the NifD sequence as susceptible to cleavage upon mitochondria import 14 , 15 . Notwithstanding these achievements, detailed analysis of yeast mitochondria-targeted Azotobacter vinelandii NifH has been hampered by low protein solubility resulting in suboptimal yields 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the NifD protein itself contains an MTPrecognition sequence, which is subject to processing, thereby making functional expression difficult. However, R98 has been identified as a key mutation for this cleavage, and an R98P mutant that is resistant to processing and retains high levels of activity in the mitochondria has been obtained [75]. Another study found that the Y100Q mutant was also resistant to processing within the plant and yeast mitochondria [76].…”
Section: Ammonia Production Using Nitrogenasementioning
confidence: 99%